BUMDes management to improve accountability and the economy of Tingal Kulon Hamlet, Wanurejo Village - Nur Laila Yuliani; Anita Viani; Tia Arfiani; Amanda Eka Adisty; Muhammad Adiatma Setyawan; Raynaldi Ahmad Assidiqy (Community Empowerment, 2022)
The purpose of the integrated community service (PPMT) activity is to provide solutions to BUMDes institutional problems related to accountability and marketing management. The targets of the program are BUMDes staff and BUMDes business units. The results are increasing accountability in BUMDes by carrying out bookkeeping using pivotables, and marketing management by utilizing social media, especially in the use of websites.